Effects of Methyl-Substituted Phenanthrolines on the Performance of Ruthenium(II) Dye-Sensitizers - Müller,Andressa V. (2015)
Tris-heteroleptic ruthenium(II) cis-[Ru(Me4-phen)(dcbH2)(NCS)2], where Me4-phen = 3,4,7,8-tetramethyl-1,10-phenanthroline, dcbH2 = 4,4'-dicarboxylic acid 2,2'-bipyridine, was synthesized, purified and characterized. Its characteristics were compared with those determined for cis-[Ru(Me2-phen)(dcbH2)(NCS)2] and cis-[Ru(phen)(dcbH2)(NCS)2] aiming to evaluate the effect of the number of methyl groups on the properties of the compounds. Changes in the Fourier transform infrared (FTIR) and 1H nuclear magnetic resonance (NMR) spectra indicated a modification in the electronic distribution of the complex because of the presence of methyl groups at the 3 and 8 positions of 1,10-phenanthroline. These changes also modified the excited state properties and resulted in a blue shift of the absorption and emission spectra. The complex was incorporated onto TiO2 to prepare dye-sensitized solar cells, achieving up to JSC = 11.9 mA cm–2, VOC = 0.627 V, ff = 0.67 and η = 5.0%.